2022
DOI: 10.3390/f13010088
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Perspective of Pine and Oak Colonization in Mediterranean Degraded Ecosystems

Abstract: Forest restoration has become one of the most important challenges for restoration ecology in the recent years. In this regard, soil fungi are fundamental drivers of forest ecosystem processes, with significant implications for plant growth and survival. However, the post-disturbance recovery of belowground communities has been rarely assessed, especially in highly degraded systems such as mines. Our aim was to compare forests and mined systems for biomass and structure of fungal communities in soil during ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
(78 reference statements)
0
8
0
Order By: Relevance
“…Tomentella sublilacina has a broad host range 81 , including bud-bursting trees, areas of afforestation 82 , 83 and temperate oak forests 84 , 85 , which suggests that this species could be involved in the recruitment process of Quercus seedlings. Although Cortinarius is known to be a highly dominant genus in old forest 86 , especially in oak stands 87 , 88 , it has also been reported to form a powerful symbiotic relationship with the Cistaceae family 71 . Cortinarius species play an important role in stand succession due to their active role in the degradation of lignin and complex organic matter 86 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tomentella sublilacina has a broad host range 81 , including bud-bursting trees, areas of afforestation 82 , 83 and temperate oak forests 84 , 85 , which suggests that this species could be involved in the recruitment process of Quercus seedlings. Although Cortinarius is known to be a highly dominant genus in old forest 86 , especially in oak stands 87 , 88 , it has also been reported to form a powerful symbiotic relationship with the Cistaceae family 71 . Cortinarius species play an important role in stand succession due to their active role in the degradation of lignin and complex organic matter 86 .…”
Section: Discussionmentioning
confidence: 99%
“…have been shown to have an increasing correlation with maturing vegetation and are predictors of tree emergence 91 , which could mean that the species mentioned above are related to the recruitment of seedlings in the succession from Cistus fields to Quercus forests. Inocybe , a well-known ECM genus that is among the first to appear after disturbances 45 , dominates soil fungal communities in holm oak ( Quercus ilex ) stands 87 . The three species of this genus that were detected most frequently in all types of forests were Inocybe krieglsteineri , Inocybe rimosa and Inocybe rufoalba.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, saprotrophic fungi derive their carbon from decomposing organic matter and are predominantly found in shallower soil layers that are abundant in carbon-rich substrates (Lindahl et al, 2007;Carteron et al, 2021;Marañoń-Jimeńez et al, 2021). In pine forests, it has been observed that the overall fungal biomass is considerably more abundant in the litter and humus layers compared to the deeper mineral zone (Adamo et al, 2022). However, in oak forests, the dominant ectomycorrhizal fungi Cortinarius and Sebacina are more prevalent in the A horizon, while saprotrophic fungi like the genus Preussia dominate the litter layer (Adamo et al, 2022).…”
Section: Microbial Activity Differs In Different Soil Horizonsmentioning
confidence: 99%
“…Finally, forest restoration has become one of the most important challenges for ecological restoration, although the post-disturbance recovery of plant-soil feedback has been rarely assessed or described. Aboveground-belowground interactions between trees and fungi are fundamental in nutrients and carbon cycles [6]. Here, biomass and structure of fungal communities were compared between P. sylvestris, Q. robur and Q. ilex (holm oak) forests and naturally revegetated mined sites to identify similarities in soil/litter inoculum between habitats to enhance tree seedlings' establishment success in degraded areas [6].…”
mentioning
confidence: 99%
“…Aboveground-belowground interactions between trees and fungi are fundamental in nutrients and carbon cycles [6]. Here, biomass and structure of fungal communities were compared between P. sylvestris, Q. robur and Q. ilex (holm oak) forests and naturally revegetated mined sites to identify similarities in soil/litter inoculum between habitats to enhance tree seedlings' establishment success in degraded areas [6]. These results showed that tree restoration strategies in degraded sites could use specific soil/litter inoculum from similar nearby forest areas upon planting/seeding, depending on tree species of interest, to provide a satisfactory soil fungal community over which to start the functional optimization between fungi and tree species dependent on the plant resources needed.…”
mentioning
confidence: 99%